دراسة واقع مؤشر أسعار استهلاك في الجزائر 2013/2021 - امجد كروش; خير الدين حميداتو (جامعة الوادي University Of Eloued, 2024)
" ملخص تهدف هذه الدراسة إلى تحليل وفهم دقيق لمؤشر أسعار الاستهلاك في الجزائر خلال الفترة من 2013 إلى 2021، بالإضافة إلى العوامل المؤثرة فيه. تم استخدام بيانات رسمية من الديوان الوطني للإحصائيات والبنك المركزي للجزائر. لتحقيق هذا الهدف، تم تطبيق أسلوب التكامل المتزامن باستخدام نموذج VAR من خلال برنامج Eviews12. وأظهرت النتائج أن الفترة المدروسة شهدت تقلبات ملحوظة في مؤشر أسعار الاستهلاك. يُعزى جزء كبير من هذه التقلبات إلى عامل التضخم، حيث وصل التضخم إلى ذروته في عام 2020 بسبب جائحة كوفيد-19." "Summary This study aims to precisely analyze and understand the Consumer Price Index (CPI) in Algeria during the period from 2013 to 2021, along with the factors influencing it. Official data from the National Office of Statistics and the Central Bank of Algeria were utilized. To achieve this objective, the cointegration method was applied using a VAR model with the help of the statistical software Eviews12. The results indicated that the studied period experienced significant fluctuations in the CPI. A major factor contributing to these fluctuations was inflation, which peaked in 2020 due to the COVID-19 pandemic."
Keywords: مؤشر أسعار الاستهلاك; التضخم; التكامل المتزامن; نموذح VAR.; Consumer Price Index; Inflation; Cointegration; VAR model